Eye Movements and White Matter are Associated with Emotional Control in Children Treated for Brain Tumors. (27th November 2020) - Moxon-Emre, Iska; Taylor, Margot J.; Farb, Norman A. S.; Oyefiade, Adeoye A.; Taylor, Michael D.; Bouffet, Eric; Laughlin, Suzanne; Skocic, Jovanka; de Medeiros, Cynthia B.; Mabbott, Donald J.
Abstract: Objective: Children treated for brain tumors often experience social and emotional difficulties, including challenges with emotion regulation; our goal was to investigate the attention-related component processes of emotion regulation, using a novel eye-tracking measure, and to evaluate its relations with emotional functioning and white matter (WM) organization. Method: Fifty-four children participated in this study; 36 children treated for posterior fossa tumors, and 18 typically developing children. Participants completed two versions of an emotion regulation eye-tracking task, designed to differentiate between implicit (i.e., automatic) and explicit (i.e., voluntary) subprocesses. The Emotional Control scale from the Behavior Rating Inventory of Executive Function was used to evaluate emotional control in daily life, and WM organization was assessed with diffusion tensor imaging. Results: We found that emotional faces captured attention across all groups ( F (1, 51) = 32.18, p < .001, η 2 p = .39). However, unlike typically developing children, patients were unable to override the attentional capture of emotional faces when instructed to (emotional face-by-group interaction: F (2, 51) = 5.58, p = .006, η 2 p = .18). Across all children, our eye-tracking measure of emotion regulation was modestly associated with the parent-report emotional control score ( r = .29, p = .045), and in patients it was associated with WM microstructure in the body and splenium of the corpus callosum (all t > 3.03, all p < .05). Conclusions: Our findings suggest that an attention-related component process of emotion regulation is disrupted in children treated for brain tumors, and that it may relate to their emotional difficulties and WM organization. This work provides a foundation for future theoretical and mechanistic investigations of emotional difficulties in brain tumor survivors.